Catalyst loaded with copper trifluoromethanesulfonate and preparation method thereof, and synthesis method of cyclohexanone-1,2-propylene glycol ketal
By using a mesoporous carbon material catalyst supported by copper trifluoromethanesulfonate, the problems of large amounts and difficulty in separation and recovery of solid acid catalysts in the preparation of cyclohexanone 1,2-propylene glycol ketal were solved, and efficient and environmentally friendly catalytic reactions were achieved, improving product purity and catalyst reuse performance.
Patent Information
- Application Number
- CN202111196804.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-14
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2041-10-14
AI Technical Summary
In the prior art, in the preparation of cyclohexanone 1,2-propylene glycol ketal, solid acid is used as the catalyst, which has problems such as large amounts, difficulty in separation and recovery, many side reactions, poor selectivity, complex post-treatment, and serious environmental pollution.
Using a mesoporous carbon material catalyst supported by copper trifluoromethylsulfonate, a mesoporous carbon material catalyst supported by contacting and reacting the mesoporous carbon material with copper trifluoromethylsulfonate in a closed reaction vessel was prepared, and cyclohexanone and 1,2 propylene glycol were contacted for synthesis reaction under heating and reflux conditions to obtain cyclohexanone-1,2 propylene glycol ketal.
This catalyst has a high conversion rate in catalytic reactions, reduces side reactions, improves product purity, and maintains high conversion rate and high selectivity after repeated use, with less environmental pollution.
Smart Images

Figure CN115970752B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalyst preparation and application, and in particular to a catalyst loaded with copper trifluoromethanesulfonate and a preparation method thereof, and a method for synthesizing cyclohexanone-1,2-propylene glycol ketal. Background Art
[0002] Cyclohexanone 1,2-propylene glycol ketal belongs to the ketal class of compounds. It has the characteristics of ketal compounds, stable chemical properties, and a fragrance that is superior to that of the parent ketone. It can be used as a fixative for fruity and woody daily fragrances, and as a coordinator in floral fragrances (He Jian, Sun Baoguo. Flavor Chemistry and Technology - Natural, Synthetic, and Blending Flavors [M]. Beijing: Chemical Industry Press, 1995: 259-260). Studies have shown that some solid acids (such as H3PW 12 O 40 、TiSiW 12 O 40 / TiO2、H3PW 12 O 40 / PAn, etc.) have a good catalytic effect on the synthesis of acetal (ketone) reaction (Luo Yumei, Yang Shuijin. Synthesis of ketal catalyzed by phosphotungstic acid catalyst [J]. Rare Metals, 2004, 28 (4): 787-789). Although solid acid catalysts have the advantages of being cheap and easy to obtain, strong acidity, high catalytic activity, and low reaction temperature, they have many problems such as large dosage, difficulty in separation, recovery and regeneration, many side reactions, poor selectivity, complex post-treatment, serious environmental pollution, corrosion of equipment, and discontinuous production process.
[0003] Therefore, if a heterogeneous catalyst with better catalytic effect is used to replace the solid acid, not only can the above defects be avoided, but also the homogeneous catalysis can be made heterogeneous. Summary of the invention
[0004] The purpose of the present invention is to overcome the problems of large dosage, difficulty in separation, recovery and regeneration, many side reactions, poor selectivity, complex post-treatment, serious environmental pollution, equipment corrosion, discontinuous production process and many other defects in the prior art in the process of preparing cyclohexanone 1,2-propylene glycol ketal by using solid acid as catalyst, and to provide a catalyst loaded with copper trifluoromethanesulfonate and a preparation method thereof, as well as a synthesis method of cyclohexanone-1,2-propylene glycol ketal. The catalyst catalyzes cyclohexanone and 1,2-propylene glycol to synthesize cyclohexanone-1,2-propylene glycol ketal, has a high conversion rate in the catalytic reaction, can reduce side reactions, improve product purity, and still maintain high conversion rate and high selectivity after repeated use, with less pollution to the environment.
[0005] In order to achieve the above-mentioned object, the first aspect of the present invention provides a mesoporous carbon material catalyst loaded with copper trifluoromethanesulfonate, wherein the catalyst comprises a mesoporous carbon material and copper trifluoromethanesulfonate loaded on the outer surface and / or inner pore wall of the mesoporous carbon material; and the specific surface area of the mesoporous carbon material is 2000-3500m 2 / g, pore volume 0.3-3.0cm 3 / g, an average pore size of 2-15nm; and based on the total weight of the catalyst, the content of the mesoporous carbon material is 50-80% by weight, and the content of the copper trifluoromethanesulfonate is 20-50% by weight.
[0006] The second aspect of the present invention provides a method for preparing the aforementioned catalyst, wherein the preparation method comprises: contacting a mesoporous carbon material, acetone and copper trifluoromethanesulfonate in a closed reaction vessel for reaction; and cooling, centrifuging and drying the reaction product to obtain a mesoporous carbon material catalyst loaded with copper trifluoromethanesulfonate.
[0007] The third aspect of the present invention provides a method for synthesizing cyclohexanone-1,2-propylene glycol ketal, wherein the synthesis method comprises:
[0008] (1) in the presence of the aforementioned catalyst, cyclohexanone and 1,2-propylene glycol are contacted under heating reflux conditions to carry out a synthesis reaction to obtain an intermediate product;
[0009] (2) The intermediate product is centrifuged to separate solid and liquid, and the obtained liquid product is distilled and separated to obtain cyclohexanone-1,2-propylene glycol acetal.
[0010] Through the above technical scheme, the present invention uses a mesoporous carbon material catalyst loaded with copper trifluoromethanesulfonate to catalyze cyclohexanone and 1,2-propylene glycol to obtain an important product in industry, cyclohexanone-1,2-propylene glycol acetal, which has a high conversion rate in the catalytic reaction, can not only reduce side reactions, improve product purity, but also maintain high conversion rate and high selectivity after repeated use, and has less environmental pollution. In addition, by using a mesoporous carbon material catalyst loaded with copper trifluoromethanesulfonate to catalyze cyclohexanone and 1,2-propylene glycol, according to gas chromatography analysis, the cyclohexanone conversion rate is 100%, the cyclohexanone-1,2-propylene glycol acetal selectivity is 96-99%, and the cyclohexanone conversion rate after four times of recycling and reuse is still 100%, and the cyclohexanone-1,2-propylene glycol acetal selectivity is 85-88%. Under the same conditions, the reaction product liquid components were analyzed by gas chromatography without adding any catalyst after the reaction, and no other products were detected. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1These are the XRD spectra of mesoporous carbon material a (a) and mesoporous carbon material catalyst A loaded with copper trifluoromethanesulfonate (b). DETAILED DESCRIPTION
[0012] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0013] The first aspect of the present invention provides a mesoporous carbon material catalyst loaded with copper trifluoromethanesulfonate, wherein the catalyst comprises a mesoporous carbon material and copper trifluoromethanesulfonate loaded on the outer surface and / or inner pore wall of the mesoporous carbon material; and the specific surface area of the mesoporous carbon material is 2000-3500m 2 / g, pore volume 0.3-3.0cm 3 / g, an average pore size of 2-15nm; and based on the total weight of the catalyst, the content of the mesoporous carbon material is 50-80% by weight, and the content of the copper trifluoromethanesulfonate is 20-50% by weight.
[0014] The inventor of the present invention unexpectedly discovered that: the present invention first utilizes a loading method to load copper trifluoromethanesulfonate on a mesoporous carbon material. The mesoporous carbon material synthesized by this method is a new type of superacid catalytic material, which shows excellent catalytic performance in the catalytic reaction. The mesoporous carbon material is used to catalyze cyclohexanone 1,2-propylene glycol ketal and obtain a reaction process in which the cyclohexanone 1,2-propylene glycol ketal product, which is important in industry, is obtained.
[0015] According to the present invention, preferably, the specific surface area of the mesoporous carbon material is 2500-3000m 2 / g, pore volume is 1.0-2.0cm 3 / g, and the average pore size is 10-14nm. In the present invention, the above-defined mesoporous carbon material is used to fully utilize the high specific surface area and large pore volume of the mesoporous carbon material to achieve uniform dispersion of the active components.
[0016] According to the present invention, preferably, based on the total weight of the catalyst, the content of the mesoporous carbon material is 55-75% by weight, and the content of the copper trifluoromethanesulfonate is 25-45% by weight. In the present invention, the use of the above-mentioned specific limited content of copper trifluoromethanesulfonate can more fully exert the structural advantages of the mesoporous carbon material and improve the performance of the catalyst.
[0017] According to the present invention, the specific surface area of the catalyst is 1000-3000m2 / g, pore volume 0.2-2.0cm 3 / g, with an average pore size of 2-13nm; preferably, the specific surface area of the catalyst is 1500-2700m 2 / g, pore volume 0.5-1.3cm 3 / g, with an average pore size of 6-10 nm; more preferably, a pore volume of 0.6-1.3 cm 3 / g.
[0018] The second aspect of the present invention provides a method for preparing the aforementioned catalyst, wherein the preparation method comprises: contacting a mesoporous carbon material, acetone and copper trifluoromethanesulfonate in a closed reaction vessel for reaction; and cooling, centrifuging and drying the reaction product to obtain a mesoporous carbon material catalyst loaded with copper trifluoromethanesulfonate.
[0019] According to the present invention, preferably, the mesoporous carbon material is preliminarily subjected to vacuum drying treatment, wherein the conditions of the vacuum drying treatment include: a temperature of 120-180° C. and a time of 2-16 hours.
[0020] According to the present invention, the mass ratio of the mesoporous carbon material, the acetone and the copper trifluoromethanesulfonate is 1:(1-12):(0.1-16); preferably, the mass ratio of the mesoporous carbon material, the acetone and the copper trifluoromethanesulfonate is 1:(3-10):(0.5-3).
[0021] According to the present invention, the contact reaction conditions include: temperature of 25-100° C., time of 1-72 h; preferably, temperature of 40-80° C., time of 3-24 h.
[0022] According to the present invention, the drying treatment conditions include: temperature of 25-200° C., time of 1-24 h; preferably, temperature of 60-150° C., time of 2-10 h.
[0023] According to the present invention, the method further comprises drying the solid phase product obtained by centrifugal solid-liquid separation to obtain a recovered catalyst, wherein the drying conditions include: vacuum drying at a temperature of 25-200° C. for 1-24 hours to obtain a recovered catalyst.
[0024] According to a particularly preferred embodiment of the present invention, a method for preparing a mesoporous carbon material catalyst loaded with copper trifluoromethanesulfonate comprises:
[0025] The mesoporous carbon material is vacuum dried at 120-150° C. for 6-8 h and cooled to room temperature;
[0026] Step 1, mesoporous carbon material: acetone: copper trifluoromethanesulfonate = 1: (1-12): (0.1-16), stirring at 25-150° C. for 1-72 h;
[0027] In step 2, the product is cooled to room temperature and centrifuged to obtain a solid product of mesoporous carbon material containing copper sulfonate.
[0028] In the present invention, in the second step, after centrifugal separation, vacuum drying is performed at 25-200° C. for 1-24 h to obtain the mesoporous carbon material solid product containing copper trifluoromethanesulfonate of the present invention.
[0029] The third aspect of the present invention provides a method for synthesizing cyclohexanone-1,2-propylene glycol ketal, wherein the synthesis method comprises:
[0030] (1) in the presence of the aforementioned catalyst, cyclohexanone and 1,2-propylene glycol are contacted under heating reflux conditions to carry out a synthesis reaction to obtain an intermediate product;
[0031] (2) The intermediate product is centrifuged to separate solid and liquid, and the obtained liquid product is distilled and separated to obtain cyclohexanone-1,2-propylene glycol acetal.
[0032] According to the present invention, the mass ratio of the cyclohexanone, the 1,2-propylene glycol and the catalyst is 1:(1-10):(0.01-0.3); preferably, the mass ratio of the cyclohexanone, the 1,2-propylene glycol and the catalyst is 1:(0.5-3):(0.05-0.2).
[0033] According to the present invention, the conditions of the synthesis reaction include: temperature of 60-150° C., time of 0.1-72 h; preferably, temperature of 70-130° C., time of 3-12 h.
[0034] According to a particularly preferred embodiment of the present invention, a method for synthesizing cyclohexanone-1,2-propylene glycol ketal comprises:
[0035] Step 1: Add cyclohexanone and 1,2-propylene glycol into the reactor, and add mesoporous carbon material containing copper sulfonate as a catalyst, according to the mass feed ratio.
[0036] Cyclohexanone: 1,2-propylene glycol: catalyst = 1: (1-10): (0.01-0.3),
[0037] Step 2, stirring the reaction for 0.1-72 hours under heating reflux and water separation conditions, cooling to room temperature, and centrifuging for solid-liquid separation;
[0038] Step 3: distill and separate the obtained liquid phase product to obtain the product cyclohexanone-1,2-propylene glycol ketal. The distillation separation adopts conventional known technology.
[0039] In addition, in the present invention, the solid phase product obtained by centrifugal solid-liquid separation in the second step is vacuum dried at a temperature of 25-200° C. for 1-24 h to obtain a recovered catalyst.
[0040] The present invention will be described in detail below through examples.
[0041] In the following examples and comparative examples:
[0042] The XRD spectrum of the sample was obtained on an X'Pert MPD X-ray powder diffractometer produced by Philips Company, using CuKα radiation, λ=0.154178 nm, and a scanning range of 2θ=0.5° to 10°.
[0043] The pore structure parameter analysis of the samples was carried out on an ASAP2020-M+C adsorption instrument purchased from Micromeritics Corporation of the United States.
[0044] Before the sample was measured, it was vacuum degassed at 350 °C for 4 h. The specific surface area of the sample was calculated using the BET method, and the pore volume was calculated using the BJH model.
[0045] The elemental analysis experiment of the samples was carried out on an EagleⅢ energy dispersive X-ray fluorescence spectrometer produced by EDAX, USA.
[0046] The drying oven was produced by Shanghai Yiheng Scientific Instrument Co., Ltd., model DHG-9030A.
[0047] The mesoporous carbon materials used in the experiment were purchased from Nanjing Xianfeng Nanomaterials Technology Co., Ltd.; the reagents used in the examples and comparative examples were purchased from Sinopharm Chemical Reagent Co., Ltd., and the reagent purity was analytical grade.
[0048] Example 1
[0049] This example is to illustrate the preparation of a mesoporous carbon material catalyst loaded with copper trifluoromethanesulfonate.
[0050] Step 1: 1 g of mesoporous carbon material a was vacuum dried at 150° C. for 6 hours, cooled to room temperature, and then 5 g of acetone and 1 g of copper trifluoromethanesulfonate were placed in a 100 ml polytetrafluoroethylene-lined reactor, the reactor was sealed, and stirred at 55° C. for 24 hours;
[0051] Step 2, after cooling to room temperature, the liquid was filtered by centrifugation to obtain a solid product, which was vacuum dried at 150° C. for 4 hours to remove impurities.
[0052] The obtained product is marked as catalyst A, and the parameter characterization and x-ray fluorescence analysis results are shown in Table 1.
[0053] Figure 1 The XRD spectra of the mesoporous carbon material (a) and the mesoporous carbon material catalyst A loaded with copper trifluoromethanesulfonate (b) are shown in Figure 2. The horizontal axis is 2θ ( ° ). It can be clearly seen from the XRD spectrum that the mesoporous carbon material still maintains a typical two-dimensional hexagonal structure after loading, and the loading process does not destroy the basic skeleton structure of the mesoporous molecular sieve.
[0054] Example 2
[0055] This example is to illustrate the preparation of a mesoporous carbon material catalyst loaded with copper trifluoromethanesulfonate.
[0056] Step 1: 1 g of mesoporous carbon material b was vacuum dried at 120°C for 16 hours, cooled to room temperature, and then 3 g of acetone and 0.5 g of copper trifluoromethanesulfonate were put into a 100 ml polytetrafluoroethylene-lined reactor, the reactor was sealed, and stirred at 40°C for 24 hours;
[0057] Step 2, after cooling to room temperature, the liquid was filtered by centrifugation to obtain a solid product, which was vacuum dried at 60°C for 10 hours to remove impurities.
[0058] The obtained product is marked as catalyst B, and the parameter characterization and x-ray fluorescence analysis results are shown in Table 1.
[0059] Example 3
[0060] This example is to illustrate the preparation of a mesoporous carbon material catalyst loaded with copper trifluoromethanesulfonate.
[0061] Step 1: 1 g of mesoporous carbon material c was vacuum dried at 180°C for 2 hours, cooled to room temperature, and then 10 g of acetone and 3 g of copper trifluoromethanesulfonate were put into a 100 ml polytetrafluoroethylene-lined reactor, the reactor was sealed, and stirred at 80°C for 3 hours;
[0062] Step 2, after cooling to room temperature, the liquid was filtered by centrifugation to obtain a solid product, which was vacuum dried at 150° C. for 2 hours to remove impurities.
[0063] The obtained product is marked as catalyst C, and the parameter characterization and x-ray fluorescence analysis results are shown in Table 1.
[0064] Table 1
[0065]
[0066] Example 4
[0067] This example is to illustrate the use of the catalyst prepared in Example 1 to prepare cyclohexanone-1,2-propylene glycol ketal.
[0068] 1.2 g of mesoporous carbon material catalyst A, 12 g of 1,2-propylene glycol and 10 g of cyclohexanone were weighed and placed in a 100 ml polytetrafluoroethylene-lined reactor in sequence, stirred at 100 ° C for 1 hour, cooled to room temperature, centrifuged, and the liquid phase components of the reaction product were analyzed by gas chromatography. The cyclohexanone conversion rate was 100%, and the cyclohexanone-1,2-propylene glycol acetal selectivity was 99%.
[0069] The solid catalyst mesoporous carbon material catalyst A was then vacuum dried at 150° C. for 6 hours, cooled to room temperature, and then recovered and reused, marked as catalyst A-recovery 1.
[0070] Example 5
[0071] This example is intended to illustrate the preparation of cyclohexanone-1,2-propylene glycol ketal using a catalyst that is recovered once.
[0072] 1.2 g of mesoporous carbon material catalyst A-recovery 1 recycled from Example 4, 12 g of 1,2-propylene glycol and 10 g of cyclohexanone were weighed and placed in a 100 ml polytetrafluoroethylene-lined reactor, stirred for 1 hour under reflux conditions, cooled to room temperature, centrifuged, and the liquid phase components of the reaction product were analyzed by gas chromatography. The cyclohexanone conversion rate was 100%, and the cyclohexanone-1,2-propylene glycol acetal selectivity was 96%.
[0073] The solid catalyst mesoporous carbon material catalyst A-recovery 1 was then vacuum dried at 150° C. for 6 hours, cooled to room temperature, and then recovered and reused, marked as catalyst A-recovery 2.
[0074] Example 6
[0075] This example is intended to illustrate the preparation of cyclohexanone-1,2-propylene glycol ketal using a secondary recovered catalyst.
[0076] 1.2 g of mesoporous carbon material catalyst A-Recovery 2 recycled from Example 5, 12 g of 1,2-propylene glycol and 10 g of cyclohexanone were weighed and put into a 100 ml polytetrafluoroethylene-lined reactor in sequence, stirred under reflux conditions for 1 hour, cooled to room temperature, and centrifuged. The liquid phase components of the reaction product were analyzed by gas chromatography. The cyclohexanone conversion rate was 100%, and the cyclohexanone-1,2-propylene glycol acetal selectivity was 92%.
[0077] The solid catalyst mesoporous carbon material catalyst A-recovery 2 was then vacuum dried at 150° C. for 6 hours, cooled to room temperature, and then recovered and reused, marked as catalyst A-recovery 3.
[0078] Example 7
[0079] This example is intended to illustrate the preparation of cyclohexanone-1,2-propylene glycol ketal using a thrice-recovered catalyst.
[0080] 1.2 g of mesoporous carbon material catalyst A-Recovery 3 recycled from Example 6, 12 g of 1,2-propylene glycol and 10 g of cyclohexanone were weighed and put into a 100 ml polytetrafluoroethylene-lined reactor in sequence, and stirred for 1 hour under reflux conditions. After cooling to room temperature, centrifugal separation was performed, and the liquid phase components of the reaction product were analyzed by gas chromatography. The cyclohexanone conversion rate was 100%, and the cyclohexanone-1,2-propylene glycol acetal selectivity was 90%.
[0081] The solid catalyst mesoporous carbon material catalyst A-recovery 3 was then vacuum dried at 150° C. for 6 hours, cooled to room temperature, and then recovered and reused, marked as catalyst A-recovery 4.
[0082] Example 8
[0083] This example is intended to illustrate the preparation of cyclohexanone-1,2-propylene glycol ketal using a catalyst that has been recycled four times.
[0084] 1.2 g of mesoporous carbon material catalyst A-Recovery 4 recycled from Example 7, 12 g of 1,2-propylene glycol and 10 g of cyclohexanone were weighed and put into a 100 ml polytetrafluoroethylene-lined reactor in sequence, and stirred for 1 hour under reflux conditions. After cooling to room temperature, centrifugal separation was performed, and the liquid phase components of the reaction product were analyzed by gas chromatography. The conversion rate of cyclohexanone was 100%, and the selectivity of cyclohexanone-1,2-propylene glycol acetal was 88%.
[0085] The solid catalyst mesoporous carbon material catalyst A-recovery 4 was then vacuum dried at 150° C. for 6 hours, cooled to room temperature, and then recovered and reused, marked as catalyst A-recovery 5.
[0086] Example 9
[0087] Cyclohexanone-1,2-propylene glycol acetal was prepared in the same manner as in Example 4, except that "catalyst A prepared in Example 1" was replaced by "catalyst B prepared in Example 2".
[0088] As a result, the cyclohexanone conversion rate was 100%, and the cyclohexanone-1,2-propylene glycol ketal selectivity was 97%.
[0089] In addition, according to the preparation method of Examples 5-8, recovered catalysts of catalyst B were used respectively, wherein the catalyst recovered once was used to prepare cyclohexanone-1,2-propylene glycol ketal, and the result was that the cyclohexanone conversion rate was 100%, and the cyclohexanone-1,2-propylene glycol ketal selectivity was 94%; the catalyst recovered twice was used to prepare cyclohexanone-1,2-propylene glycol ketal, and the result was that the cyclohexanone conversion rate was 100%, and the cyclohexanone-1,2-propylene glycol ketal selectivity was 91%; the catalyst recovered thrice was used to prepare cyclohexanone-1,2-propylene glycol ketal, and the result was that the cyclohexanone conversion rate was 100%, and the cyclohexanone-1,2-propylene glycol ketal selectivity was 89%; the catalyst recovered four times was used to prepare cyclohexanone-1,2-propylene glycol ketal, and the result was that the cyclohexanone conversion rate was 100%, and the cyclohexanone-1,2-propylene glycol ketal selectivity was 86%.
[0090] Example 10
[0091] Cyclohexanone-1,2-propylene glycol acetal was prepared in the same manner as in Example 4, except that "catalyst A prepared in Example 1" was replaced by "catalyst C prepared in Example 2".
[0092] As a result, the cyclohexanone conversion rate was 100%, and the cyclohexanone-1,2-propylene glycol ketal selectivity was 96%.
[0093] In addition, according to the preparation method of Examples 5-8, recovered catalysts of catalyst C were used respectively, wherein the catalyst recovered once was used to prepare cyclohexanone-1,2-propylene glycol ketal, and the result was that the cyclohexanone conversion rate was 100%, and the cyclohexanone-1,2-propylene glycol ketal selectivity was 93%; the catalyst recovered twice was used to prepare cyclohexanone-1,2-propylene glycol ketal, and the result was that the cyclohexanone conversion rate was 100%, and the cyclohexanone-1,2-propylene glycol ketal selectivity was 90%; the catalyst recovered thrice was used to prepare cyclohexanone-1,2-propylene glycol ketal, and the result was that the cyclohexanone conversion rate was 100%, and the cyclohexanone-1,2-propylene glycol ketal selectivity was 87%; the catalyst recovered four times was used to prepare cyclohexanone-1,2-propylene glycol ketal, and the result was that the cyclohexanone conversion rate was 100%, and the cyclohexanone-1,2-propylene glycol ketal selectivity was 85%.
[0094] Comparative Example 1
[0095] 12 g of 1,2-propylene glycol and 10 g of cyclohexanone were weighed and put into a 100 ml polytetrafluoroethylene-lined reactor in sequence, stirred under reflux conditions for 1 hour, cooled to room temperature, and centrifuged. The liquid phase components of the reaction product were analyzed by gas chromatography, and no product was detected.
[0096] Comparative Example 2
[0097] Cyclohexanone-1,2-propylene glycol acetal was prepared in the same manner as in Example 4, except that "catalyst A prepared in Example 1" was replaced by "catalyst D", which had a specific surface area of 752 m 2 / g, pore volume 0.4cm 3 / g, and the average pore size is 4nm.
[0098] As a result, the cyclohexanone conversion rate was 95%, and the cyclohexanone-1,2-propylene glycol ketal selectivity was 83%.
[0099] Comparative Example 3
[0100] Cyclohexanone-1,2-propanediol acetal was prepared in the same manner as in Example 4, except that "Catalyst A prepared in Example 1" was replaced with "Catalyst D", which was loaded with zinc chloride instead of copper trifluoromethanesulfonate.
[0101] As a result, the cyclohexanone conversion rate was 90%, and the cyclohexanone-1,2-propylene glycol ketal selectivity was 77%.
[0102] Comparative Example 4
[0103] Cyclohexanone-1,2-propylene glycol acetal was prepared in the same manner as in Example 4, except that "catalyst A prepared in Example 1" was replaced with "catalyst E, wherein the content of the mesoporous carbon material is 85 wt %, and the content of the copper trifluoromethanesulfonate is 15 wt %, based on the total weight of the catalyst".
[0104] As a result, the cyclohexanone conversion rate was 86%, and the cyclohexanone-1,2-propylene glycol ketal selectivity was 72%.
[0105] It can be seen from the above experimental results that the catalyst prepared by the method of the present invention has a significantly better effect in the synthesis reaction of cyclohexanone-1,2-propylene glycol ketal. Compared with conventional ketal catalysts, the catalyst provided by the present invention can improve the raw material conversion rate and cyclohexanone-1,2-propylene glycol ketal selectivity.
[0106] Since the catalyst of the present invention was not used in Comparative Example 1, no product was generated.
[0107] Since comparative example 2 used a catalyst with smaller specific surface area, pore volume and average pore diameter, the active components were unevenly distributed, resulting in lower cyclohexanone conversion and lower selectivity for cyclohexanone-1,2-propylene glycol acetal.
[0108] In Comparative Example 3, copper triflate is not loaded in the catalyst, but zinc chloride is loaded as the active component. Since the catalytic activity of zinc chloride of the same weight is lower than that of copper triflate, the conversion rate of cyclohexanone is lower and the selectivity of cyclohexanone-1,2-propylene glycol acetal is lower.
[0109] In Comparative Example 4, the content of the carrier in the catalyst is too high, and the content of the active component copper trifluoromethanesulfonate is too low. Due to the insufficient active components in the reaction, the cyclohexanone conversion rate is low and the selectivity of cyclohexanone-1,2-propylene glycol acetal is low.
[0110] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A mesoporous carbon material catalyst loaded with copper trifluoromethanesulfonate, characterized in that: The catalyst comprises a mesoporous carbon material and copper trifluoromethanesulfonate supported on the outer surface and / or inner pore wall of the mesoporous carbon material; and the specific surface area of the mesoporous carbon material is 2000-3500m 2 / g, pore volume 0.3-3cm 3 / g, an average pore size of 2-15nm; and based on the total weight of the catalyst, the content of the mesoporous carbon material is 50-80% by weight, and the content of the copper trifluoromethanesulfonate is 20-50% by weight.
2. The catalyst according to claim 1, wherein The specific surface area of the mesoporous carbon material is 2500-3000m 2 / g, pore volume is 1-2cm 3 / g, and the average pore size is 10-14nm.
3. The catalyst according to claim 1, wherein Based on the total weight of the catalyst, the content of the mesoporous carbon material is 55-75% by weight, and the content of the copper trifluoromethanesulfonate is 25-45% by weight.
4. The catalyst according to any one of claims 1 to 3, wherein The specific surface area of the catalyst is 1000-3000m 2 / g, pore volume 0.2-2cm 3 / g, and the average pore size is 2-13nm.
5. The catalyst according to claim 4, wherein The specific surface area of the catalyst is 1500-2700m 2 / g, pore volume 0.5-1.3cm 3 / g, and the average pore size is 6-10nm.
6. A method for preparing the catalyst according to any one of claims 1 to 5, characterized in that: The preparation method comprises: contacting a mesoporous carbon material, acetone and copper trifluoromethanesulfonate in a closed reaction container for reaction; and cooling, centrifuging and drying the reaction product to obtain a mesoporous carbon material catalyst loaded with copper trifluoromethanesulfonate.
7. The method according to claim 6, wherein: The mass ratio of the mesoporous carbon material, the acetone and the copper trifluoromethanesulfonate is 1:(1-12):(0.1-16).
8. The method according to claim 6, wherein: The conditions for the contact reaction include: temperature of 25-100° C. and time of 1-72 h; And / or, the drying treatment conditions include: temperature of 25-200° C. and time of 1-24 h.
9. The method according to claim 6, wherein: The method further comprises drying the solid phase product obtained by centrifugal solid-liquid separation to obtain a recovered catalyst.
10. A method for synthesizing cyclohexanone-1,2-propylene glycol ketal, characterized in that: The synthesis method comprises: (1) in the presence of the catalyst according to any one of claims 1 to 5, under heating reflux conditions, contacting cyclohexanone and 1,2-propylene glycol to carry out a synthesis reaction to obtain an intermediate product; (2) The intermediate product is centrifuged to separate solid and liquid, and the obtained liquid product is distilled and separated to obtain cyclohexanone-1,2-propylene glycol acetal.
11. The synthesis method according to claim 10, wherein The mass ratio of the cyclohexanone, the 1,2-propylene glycol and the catalyst is 1:(1-10):(0.01-0.3); And / or, the conditions of the synthesis reaction include: temperature of 60-150° C. and time of 0.1-72 h.
Citation Information
Patent Citations
Large-aperture SBA-15 mesoporous material-copper trifluoromethanesulfonate composite catalyst, preparation method and application
CN101862676A
Supported copper (II) trifluoromethanesulfonate catalyst, preparation method and application thereof, and cyclohexanone ethylene ketal preparation method
CN103586086A